Clinicopathological and Prognostic Value of S100A4 Expression in Gastric Cancer: A Meta-Analysis. Issue 2 (April 2014) - Ling, Zhian; Li, Ruolin
Purposes: For several years S100A4 has been implicated in tumor progression and prognosis. However, the prognostic value of S100A4 overexpression in patients with gastric cancer remains unknown. Therefore, we performed a meta-analysis to assess the relationship between S100A4 overexpression and clinical outcome of gastric cancer. Methods and Results: Candidate studies were searched from PubMed, Embase, Cochrane Library, and ISI Web of Science. We included studies that evaluated the prognostic value of S100A4 expression in gastric cancer patients with regard to survival and a series of clinicopathological parameters. The pooled hazard ratios (HR) and odds ratios (OR) with 95% confidence intervals (CI) were used to estimate the effects. Ten studies, all from Asia, were included in the meta-analysis. The pooled analysis showed that S100A4 overexpression was significantly associated with worse overall survival (OS) (HR=1.86, 95% CI: 1.45-2.38, p<0.00001) without heterogeneity in the data (I 2 =43.6%, p=0.131). Furthermore, our results showed that S100A4 overexpression was significantly correlated with some clinicopathological parameters such as tumor grade, stage, metastasis, invasion, and relapse. Conclusions: The results of our meta-analysis indicate that S100A4 overexpression correlates with more adverse clinical features and a poor prognosis of gastric cancer patients in Asia, thus suggesting that S100A4 could be a useful marker to evaluate progression and prognosis of Asian gastric cancer patients. More studies from Western countries with a larger number of tumors and standardized methods are required before significant conclusions can be drawn.